2014
DOI: 10.1108/jm2-11-2011-0057
|View full text |Cite
|
Sign up to set email alerts
|

Using portfolio optimisation models to enhance decision making and prediction

Abstract: Purpose – The purpose of this paper is to analyse and compare the performances of portfolio optimisation models including Markowitz's mean-variance model (MV model), Konno and Yamazaki's mean-absolute deviation portfolio optimisation model (MAD model), Young's minimax portfolio model and the VaR model. Design/methodology/approach – Historical data on 43 constituent shares listed on the Hong Kong Hang Seng Index (HSI) covering a four-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…He showed that statistically optimum portfolio can be created. After his marvellous contribution in the field of finance, many researchers started using various statistical measures (Bauder et al, 2020; Bodnar et al, 2021; Chau Li et al, 2012; Cura, 2009; Garcia et al, 2020; Rancovic et al, 2016; Roy, 2016; Siaw et al, 2017) to get optimum portfolio. In the selection of optimum portfolio, few issues are important viz.…”
Section: Introductionmentioning
confidence: 99%
“…He showed that statistically optimum portfolio can be created. After his marvellous contribution in the field of finance, many researchers started using various statistical measures (Bauder et al, 2020; Bodnar et al, 2021; Chau Li et al, 2012; Cura, 2009; Garcia et al, 2020; Rancovic et al, 2016; Roy, 2016; Siaw et al, 2017) to get optimum portfolio. In the selection of optimum portfolio, few issues are important viz.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have been done in the literature in different fields of this domain. Li et al (2014), in their work, analyzed and compared the performances of portfolio optimization models, including Markowitz’s mean variance (MV) model, Konno and Yamazaki’s mean absolute deviation (MAD) portfolio optimization model, Young’s minimax portfolio model and the value at risk (VaR) model. Numerical results with 43 shares listed on the Hong Kong Hang Seng Index (HSI) indicated that different levels of required annual returns impact portfolio composition.…”
Section: Introductionmentioning
confidence: 99%
“…Capturing the salient features of the time-series price data is an important consideration also for investment decisions (Najafabadi et al, 2020) and the characteristics of financial market data in general for other financial modelling endeavours. Basilio et al (2018) for identifying how a multi-criteria analysis may assist investment portfolios formation; Chau et al (2014) for showing the impact of historical data on determination of portfolio composition and the effect of required return on optimisation models' performance; and Sawicki (2009) for finding an explanation regarding the presence of size premium in equity markets using time series data of mutual funds. In Heidari-Fathian and Davari-Ardakani (2019), a portfolio selection problem is tackled in which the portfolio's net present value is maximised and the resource-usage variation is minimised between successive time periods.…”
Section: Introductionmentioning
confidence: 99%